2023
DOI: 10.3390/tropicalmed8020124
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Changes in Hepatic Sinusoidal Endothelial Cells in Schistosoma japonicum-Infected Mice

Abstract: Schistosomiasis japonica is a zoonotic parasitic disease causing liver fibrosis. Liver sinusoidal endothelial cells (LSECs) exhibit fenestrations, which promote hepatocyte regeneration and reverses the process of liver fibrosis. To investigate the pathological changes of LSECs in schistosomiasis, we established a Schistosomiasis model. The population, phenotype, and secretory function of LSECs were detected by flow cytometry at 20, 28, and 42 days post infection. The changes in LSEC fenestration and basement m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Shao et al [ 76 ] reported that BRG1 suppressed eNOS activity and reduced the bioavailability of NO in LSECs by regulating the vascular secretion signaling of LSECs, contributing to the worsening of liver fibrosis. Similarly, Jiang et al [ 77 ] reported that the infection with schistosoma japonicum resulted in decreased differentiation and increased LSEC dedifferentiation, along with reduced NO secretion and enhanced TGF-β secretion. Meanwhile, several chemical and natural compounds have shown great anti-fibrosis effects via modulating the NO signaling.…”
Section: Remodeling Of Intracellular Pathways For Lsec Homeostasis Ba...mentioning
confidence: 98%
“…Shao et al [ 76 ] reported that BRG1 suppressed eNOS activity and reduced the bioavailability of NO in LSECs by regulating the vascular secretion signaling of LSECs, contributing to the worsening of liver fibrosis. Similarly, Jiang et al [ 77 ] reported that the infection with schistosoma japonicum resulted in decreased differentiation and increased LSEC dedifferentiation, along with reduced NO secretion and enhanced TGF-β secretion. Meanwhile, several chemical and natural compounds have shown great anti-fibrosis effects via modulating the NO signaling.…”
Section: Remodeling Of Intracellular Pathways For Lsec Homeostasis Ba...mentioning
confidence: 98%